Una (meta) crítica a las escuelas contemporáneas de desarrollo - Manuel Antonio JIMÉNEZ-CASTILLO (Revista Iberoamericana de Estudios de Desarrollo)
Throughout this article we will discuss some epistemological limitations that the main contemporary theories of development face. We will examine how despite such theories bases their assumptions from an individual perspective, development literature has traditionally tend to move away to complexity by a theoretical assimilation of personal utility´s maximalization proposition. Such was possible since Kant´s note a transgression of becoming ends into means of development. This perspective particularly assumed by human development theory is replaced by an epistemological reductionism based on individual and social justice as conceptual abstractions.